Conclusions: Future and perspective toward direct images with kilometric meta-apertures. Issue 69 (10th September 2015) - Labeyrie, A.
Abstract : The recent years have seen a spectacular progress of angular resolution in optical astronomy, with increasingly long interferometric baselines becoming used at several sites. However, the limiting magnitudes have remained modest, in spite of the large apertures used at instruments such as the VLTI. Much cutting-edge science remains to be performed with the VLTI, but the time has come for a new generation of interferometer systems exploiting many apertures.